Modelling of Strain Field in Extrusion by Die Geometry - Libura, W. (Engineering Transactions, 1995)
The strain distributions within the deformation zone and the total strain in the extruded product cross-sections for A1Cu4Mg alloy were determined. The visioplasticity method was used in calculations. The plane indirect mode of extrusion was performed with variable die geometry. The strain distribution within the deformation zone can be affected by the shape of the die and in this way, the material structure can be controlled. The range of deformation zone depends on the die used. The most uniform strain distribution and material structure were obtained when the so-called convex-faced die was applied.